Two human metabolites rescue a C. elegans model of Alzheimer’s disease via a cytosolic unfolded protein response - Priyanka Joshi (Nature Portfolio, 2021)
Joshi et al. identify two human metabolites, carnosine and kynurenic acid, that rescue a C. elegans model of Alzheimer’s disease by inhibiting the aggregation of the amyloid beta peptide in vivo. They find that these metabolites trigger a cytosolic unfolded protein response through the transcription factor HSF-1 and molecular chaperones DNJ-12 and DNJ-19, thus providing mechanistic links between metabolite homeostasis and protein homeostasis to further insights into interventions against neurodegenerative diseases.